PEMBELAJARAN AKIDAH AKHLAK DI MADRASAH ALIYAH AL HIDAYAH DONOWARIH KARANGPLOSO MALANG - Dewy Nur Fitriana; Ilyas Thohari; Yorita Febry Lismanda (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Strategy of akidah akhlak for madrasah aliyah student is an act of training students minds in such a way that in life attitudes and actions are influenced by spiritual values. Madrasah Aliyah Al Hidayah Donowarih Karangploso Malang is an Al Hidayah boarding school in Karangploso Malang, which incidentally is an institution under the auspices of a boarding school that want students and student who have rapid scientific development but still uphold the value of morality akhlaqul karimah. The purpose of this research is to describe the teacher’s strategy in planning, implementing and evaluating the learning of the moral code of learning in Madrasah Aliyah Al Hidayah Donowarih Karangploso Malang. This research uses a descriptive qualitative approach. The method use is observation, interview, and documeantation. The result of this study include the learning planning strategy for the subjects of the Madrasah Aliyah Al Hidayah Donowarih Karangploso Malang, before implementing the learning process, namely compiling the lesson plans, and learning scenarios, the learning implementation strategies, including introductory activities, core activities, and closing activities, evaluation of learning strategies the study of the Akidah Akhlak in Madrasah Aliyah Al Hidayah Donowarih Karangploso Malang uses two evaluations namely through the evaluation of attitudes and evaluating work on the questions. From the results of the two evaluations then the final grade is taken which is evidence of student learning outcomes that will be reported to the student’s guardian in the form of report cards.